Na drogach świętości. Intelektualno−duchowa sylwetka Karola Wojtyły–Jana Pawła II - SZOSTEK, Andrzej (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2011)
Speaking of the holiness of an eminent person is always risky, since holiness is in every case part of the sphere of the human being’s intimate contact with God, to which no «outsider» has access. I nevertheless dare present some – deeply personal – remarks on the subject of the holiness of John Paul II, because he himself as if encouraged it by the fact that he was living his life before the eyes of the world, accepting that he was constantly being watched by others. It was striking first of all that he practised responsible conscientiousness in the realization of the mission which had been entrusted to him and which he had accepted as his personal task. On numerous occasions Karol Wojtyła–John Paul II demonstrated that he perceived every challenge in his life as part of the mission given to him ultimately by God himself. In this sense, one might say, he did not distinguish the religious dimension of his life from what constituted the field of his work. Secondly, it was characteristic of him that he always sought the fullness of truth: even in the case of ideas he put under criticism, he would always explore them in order to find any elements that might turn out pertinent, and he wanted a vision of the human being and of morality that would take into consideration a broad panorama of approaches, opening one up to the fullness of God himself. Thirdly, and most importantly, John Paul II was above all seeking God and continually offering his life to God. His pontifical motto Totus Tuus evoked the holy Virgin Mary, but his genuine Marian devotion had a Christocentric bent: he considered the Holy Virgin Mary a paragon to follow and wanted to be stand− ing under the cross of Christ together with her, and – like her – to lead all hu− man persons towards Christ, who has genuinely loved them. Translated by Dorota Chabrajska Lecture delivered at the symposium “John Paul: The Calling to Holiness,” held by the John Paul II Institute at the Catholic University of Lublin on 4 November 2010.